2017
DOI: 10.1002/ange.201708003
|View full text |Cite
|
Sign up to set email alerts
|

Transition‐Metal‐Free Catalytic Hydrodefluorination of Polyfluoroarenes by Concerted Nucleophilic Aromatic Substitution with a Hydrosilicate

Abstract: At ransition-metal-free catalytic hydrodefluorination (HDF) reaction of polyfluoroarenes is described. The reaction involves direct hydride transfer from ahydrosilicate as the key intermediate,w hichi sg enerated from ah ydrosilane and af luoride salt. The eliminated fluoride regenerates the hydrosilicate to complete the catalytic cycle.D ispersioncorrected DFT calculations indicated that the HDF reaction proceeds through ac oncerted nucleophilic aromatic substitution (CS N Ar) process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 70 publications
2
11
0
1
Order By: Relevance
“…120 S N Ar reactions spanning a range of ring types (benzene, (NO 2 ) n=1,2,3 -benzene, H 3 C-C=O-benzene, pyridine, pyrazine, pyrimidine), nucleophiles (F − , MeO − , N 3 − , Me2N − , formate − ), and leaving groups (F − , Cl − , Br − ) were thoroughly examined at B3LYP-D3(BJ)/6–31+G*/PCM(DMSO). Consistent with previous studies, 3950 in all but 21 cases, it was not possible to locate a Meisenheimer intermediate by beginning optimizations in the expected neighborhood of the intermediate. Intrinsic reaction coordinate (IRC) searches were attempted for each reaction.…”
Section: Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…120 S N Ar reactions spanning a range of ring types (benzene, (NO 2 ) n=1,2,3 -benzene, H 3 C-C=O-benzene, pyridine, pyrazine, pyrimidine), nucleophiles (F − , MeO − , N 3 − , Me2N − , formate − ), and leaving groups (F − , Cl − , Br − ) were thoroughly examined at B3LYP-D3(BJ)/6–31+G*/PCM(DMSO). Consistent with previous studies, 3950 in all but 21 cases, it was not possible to locate a Meisenheimer intermediate by beginning optimizations in the expected neighborhood of the intermediate. Intrinsic reaction coordinate (IRC) searches were attempted for each reaction.…”
Section: Methodssupporting
confidence: 86%
“…3034 In the context of S N Ar reactions, Williams et al have shown that the quasi-symmetric 1 addition of substituted phenoxides to phenoxytriazines is concerted, 35,36 while the apparently analogous addition of pyridines to pyridyltriazines is stepwise. 37,38 For many other reactions, computations 3950 predict concerted mechanisms, contradicting the textbook view that S N Ar reactions proceed via stepwise addition-elimination mechanisms. 51…”
mentioning
confidence: 93%
“…The fluorine atom at the p -position of the trifluoromethyl group of octafluorotoluene was substituted by phenothiazine, without the formation of regioisomers or multisubstituted products. The observed regioselectivity was in agreement with previously reported outcomes of octafluorotoluene S N Ar [ 11 , 13 ], and it is governed by the electron density at the reactive carbons ( ortho - and para -positions) on the aromatic ring and the steric repulsion between the trifluoromethyl group and bulky phenothiazine. The K 2 CO 3 /DMF system was found to be an efficient combination for mono S N Ar between various phenothiazines and octafluorotoluene ( Scheme 3 ).…”
Section: Resultssupporting
confidence: 91%
“…Polyfluoroarenes react with organometallic compounds, such as organolithium or organomagnesium reagents, to convert aromatic C-F bonds into C-C bonds without the use of transition metal catalysts [ 7 , 8 ]. The combination of a fluoride salt and organosilane compounds as nucleophiles has also been successful in the S N Ar of polyfluoroarenes, wherein the reaction proceeds with a catalytic amount of a fluoride anion [ 9 , 10 , 11 , 12 , 13 ]. The use of alcohols or amines as nucleophiles enables C-O and C-N bond formation to produce the corresponding aryl ether and aniline derivatives [ 8 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“… 8 HDFs have largely been dominated by transition-metal catalysis, 9 , 10 and a considerable number of these systems proceed through the catalytic steps depicted in Figure 1 A. 10 Recent progress in HDFs extended the available strategies to photoredox catalysis 11 and main-group catalysis, 12 , 13 which proceed through mechanistically distinct catalytic steps. In addition to its synthetic potential, HDF serves as a model reaction for studying the performance of main-group compounds in the elementary organometallic steps of a catalytic cycle.…”
mentioning
confidence: 99%